Synthesis and characteristics of ionic liquid-implanted HKUST-1 metal-organic frameworks for transforming heat into extraordinary water transfer - Han, Bo (2024)
This paper proposes ionic liquid (IL)-embedded HKUST-1 metal-organic frameworks (MOFs) to boost water transfer for transforming waste heat into work. First, the parent HKUST-1 is synthesized and encapsulated with different types of ionic liquids and various embedment ratios. Second, the parent and modified HKUST-1 MOFs are characterized via XRD, FTIR, TGA, SEM, and N2 adsorption techniques. Third, the water adsorption characteristics on these synthesized MOFs are experimented for a wide temperature and pressure range. By embedding ionic liquids, the following are found: (i) The cyclic water adsorption stability is significantly improved. (ii) The water adsorption isotherms of the parent HKUST-1 are revised. (iii) The limiting water capacity is increased up to 0.58 g/g (69.1% more than the parent HKUST-1). (iv) The adsorption and desorption rates are accelerated (28%/ 30% higher). (v) The water transfer is boosted up to 0.45 kg/kg, which is 84% more than that of the parent HKUST-1 MOFs. These findings confirm the feasibility of low temperature (≤70 °C) and short operation cycle (≤500 s) assisted adsorption heat transformation applications.